Analysis of Digital Transformation Strategies and Product Innovation to Enhance Competitive Advantage in Fisheries MSMEs to Support the Blue Economy in Kendal Regency - Ridho, Ali; Rachmawati, Dwi (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the influence of digital transformation and product innovation on the competitive advantage of fish processing MSMEs in Kendal Regency to support the Blue Economy. Kendal has significant potential in aquaculture, particularly milkfish, but faces challenges such as marketing, technology adoption, and business management. A deductive approach with a survey method was employed to collect primary data through questionnaires distributed to 278 MSME actors. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that product innovation significantly influences competitive advantage with a coefficient of 0.831 (p < 0.05), and digital transformation also has a significant influence with a coefficient of 0.060 (p < 0.05). Together, product innovation and digital transformation explain 74.6% of the variability in competitive advantage. Therefore, it is recommended that MSMEs enhance their product innovation capacity through diversification and added value development, as well as leverage digital transformation using e-commerce platforms and social media to expand market access. This study contributes to the development of strategies for Kendal’s fishery MSMEs to support the Blue Economy and achieve sustainable competitive advantage.